Hepatocyte Nuclear Factor 1 Beta Mutation-associated Newborn Onset of Glomerulocystic Kidney Disease: A Case Presentation - Nilüfer Göknar; Melda Ekici Avcı; Diana Üçkardeş; Emre Keleşoğlu; Kübra Tekkuş Ermiş; Cengiz Candan (Medeniyet Medical Journal)
Mutations in hepatocyte nuclear factor-1 beta (HNF1B) are the most commonly identified genetic cause of renal malformations. Heterozygous mutations are associated with renal cysts and diabetes syndrome. Various renal developmental abnormalities and maturity-onset diabetes of the young could be the presenting factors of these mutations. A 10-year-old boy who was evaluated for bilateral cystic kidneys and chronic kidney disease from the newborn period was diagnosed with HNF1B-related glomerulocystic disease by DNA sequencing. The differential diagnosis of autosomal dominant polycystic kidney disease was a diagnostic pitfall. The genetic screening of the family revealed his mother, sister, and brother to have the same mutation. Therefore, genetic diagnosis and counseling are important for cystic kidney diseases not only for formulating the diagnosis and early management plan but also for the diagnosis of potential asymptomatic cases in the family.